Who Cares about the Health of Health Care Professionals? An 18-Year Longitudinal Study of Working Time, Health, and Occupational Turnover. (August 2016) - Kramer, Amit; Son, Jooyeon
Health care workers are employed in a complex, stressful, and sometimes hazardous work environment. Studies of the health of health care workers tend to focus on estimating the effects of short-term health outcomes on employee attitudes and performance, which are easier to observe than long-term health outcomes. Research has paid only scant attention to work characteristics that are controlled by the employer and its employees, and their relationship to employees' long-term physical health and organizational outcomes. The authors use data from the National Longitudinal Survey of Youth (NLSY) from 1992 to 2010 to estimate the relationships among working time, long-term physical health, job satisfaction, and turnover among health care employees. Using a between- and within-person design, they estimate how within-person changes in work characteristics affect the within-person growth trajectory of body mass index (BMI) over time and the relationship between working-time changes and physical health, and occupational turnover. The study finds that health care employees who work more hours suffer from a higher level of BMI and are more likely to leave their occupation.